Применение капиллярных световодов в спектроскопии - Лазаренко, Анатолий Григорьевич; Андреев, Александр Николаевич (НТУ "ХПИ", 2003)
The review of different capillary light guides applications in spectroscopy. Newely developed capillaries with light guiding properties with water solutions fillings main features and applications methods are discussed. Theoretical possibilities of capillary light guides application in correlation spectroscopy particles sizes determination are shown
Keywords: оптические измерения; рассеянный свет; отражение; кварцевые капиллярные световоды; люминесценция; люминофор; лазерное излучение